Penerapan Strategi Pembelajaran Time Token Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS Kelas V MI Miftahul Huda Lamongan - Wahidah Puspa Dina (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2017)
The research based on the low outcomes of fifth class student in Islamic elementary school MI Miftahul Huda in social studies learning. From the 11 students, 6 students didn’t complete in the daily tests. Therefore it is very necessary to apply a strategy that is considered to improve student learning outcomes, one such strategy is time token learning strategy. Time token trategy are appropriate because they have many the advantages and in accordance with characteristic of students.The purpose of this research that is, to know the application of time token strategy learning in improve learning outcomes students in social class and to know the increase in study results the students in learning social class. This research is using Kurt Lewin's research methods. The methods consisted of two cycles. Classroom Action Research can be improve the learning outcomes if; 1) 90 percent of students or more included in a category be completed, 2) minimal criteria for learning outcomes in social class fifth grade is as much as 75, and 3) Teachers can implement learning as planned the basis of 85%. Frome the Criteria above, time token learning strategy can improve learning outcomes can be seen from the observation of the teacher in the learning activities in the first cycle increased by 72% in the second cycle of 91%. In addition, viewed from the observation of student activity in the first cycle the percentage gain of 64% in the second cycle increased by 80%. At the first cycle of the average student values is 72, with a percentage of 64% completeness. At the first cycle there are seven students who completed and 4 students who do not complete. At the second cycle the average student values 83, with a percentage of 91% completeness. At the second cycle there are 10 students who completed and only 1 student who does not complete, so it does not need to be held the third cyclKeywords: Strategy Time Token, Social studies Learning Outcomes, Classroom Action Research